2017
DOI: 10.1186/s13046-017-0610-5
|View full text |Cite
|
Sign up to set email alerts
|

PAK5-mediated phosphorylation and nuclear translocation of NF-κB-p65 promotes breast cancer cell proliferation in vitro and in vivo

Abstract: BackgroundAbnormal proliferation is significantly associated with the promotion of malignant tumor. Growing evidence suggest that the signal pathways of p21cdc42/rac1-activated kinase 5 (PAK5) have been found in various tumor progression, however, the role of PAK5 in breast cancer remains largely unclear.MethodsWe evaluated PAK5 and p65 staining in breast cancer tissues (BCTs) and paired non-cancerous tissues (NTs) using tissue microarray (TMA) technology. The functions of PAK5 were studied in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…PAK5‐directed GATA1 phosphorylation has been reported to induce epithelial–mesenchymal transition in breast cancer cells . In addition, PAK5 facilitates breast cancer cell proliferation by phosphorylating NF‐κB‐p65 . Although studies have suggested that PAK5 is a key regulator of breast cancer progression, the underlying molecular mechanism remains incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…PAK5‐directed GATA1 phosphorylation has been reported to induce epithelial–mesenchymal transition in breast cancer cells . In addition, PAK5 facilitates breast cancer cell proliferation by phosphorylating NF‐κB‐p65 . Although studies have suggested that PAK5 is a key regulator of breast cancer progression, the underlying molecular mechanism remains incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB p65 is a well-recognized anti-apoptotic transcription factor and abnormal expression or activation of NF-κB p65 has been found in multiple types of malignant cancers such as cervical cancer, esophageal squamous cancer, ovarian cancer, breast cancer and glioma et al [13,[26][27][28][29]. NF-κB promotes tumorigenesis and therapy resistance mainly through induction of master transcription factors including signal transducer and activator of transcription 3 (STAT3) and TAZ [30].…”
Section: Discussionmentioning
confidence: 99%
“…PAK7 was originally found in brain in which promotes the formation of filopodia in nerve cells 9 . However, recent studies have found that the expression level of PAK7 significantly increased in colorectal cancer 10 , 11 , ovarian cancer 12 , gastric cancer 13 - 15 , Neuroglioma 16 , 17 , Hepatocellular carcinoma 18 , 19 , Pancreatic cancer 20 , 21 , Osteosarcoma 22 , and breast cancer 23 - 25 , leading to increased proliferation and migration of tumor cells and inhibition of apoptosis. More importantly, PAK7 expression was positively correlated with the malignancy of colorectal cancer and ovarian cancer, suggesting that PAK7 indeed played an important role in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that PAK7 could phosphorylate GATA-binding factor 1 (GATA1) to recruit more Histone deacetylases 3/4 (HDA3/4) to E-cadherin promoter region, resulting in suppression of E-cadherin expression, which leads to epithelial-mesenchymal transition in breast cancer cells 23 . PAK7 can promote the phosphorylation and the nuclear translocation of p65 subunit of nuclear factor-kappaB (NF-κB), therefore promoting the proliferation and cell-cycle progression in breast cancer by increasing the expression of cyclin D1 in vitro and in vivo 25 . In addition, another study also reveals the PAK5-Egr1-MMP2 signaling pathway to be a critical regulator of cell migration and invasion in breast cancer cell 24 .…”
Section: Introductionmentioning
confidence: 99%